Establish a new parameter “horizontal view-axial angle” and explore its role in the treatment of atlantoaxial instability diseases - Huang, Hongxiang; Sheng, Minfeng; Zeng, Guangliang; Sun, Chao; Li, Rujun (Frontiers in Surgery, 2023)
Objective: To establish a new parameter that can be clearly measured on X-ray images to complement the description of the sagittal alignment of the craniocervical junction. The authors expects that this new parameter will enhance surgeons’ understanding of the sagittal alignment of the craniocervical junction and play a positive role in the guidance of intraoperative reduction and in the evaluation of postoperative outcomes of patients with atlantoaxial instability.Methods: From November 2018 to June 2020, a total of 159 subjects who underwent frontal and lateral cervical X-ray examination in the Second Affiliated Hospital of Soochow University were included in the study. Age, gender, previous spinal trauma and disease history of each subject were recorded. After screening, 127 effective samples were finally obtained. When taking lateral cervical radiographs, all subjects placed their neck in a neutral position and looked straight ahead with both eyes. On the obtained lateral X-ray images, a straight line was drawn from the most depressed point of the nasal bone to the anterior clinoid process, another line was made along the posterior edge of the C2 vertebral body, and the angle between the two lines was measured, which was defined as “Horizontal view-axial angle”. The angle formed by the tangent of the posterior edge of the C2 vertebra and C7 vertebral body is the "C2-C7 angle", which was used to describe the curvature of the lower cervical vertebra. The normal range of horizontal view-axial angle and its relationship with C2-7 angle were evaluated.Results: The average C2-C7 angle of male subjects was(14.0±7.4)°, while that of female subjects was（11.09±7.36）°. The average horizontal view-axial angle of male subjects was (92.79 ±4.52) °, and that of female subjects was (94.29 ±4.50) °. Pearson correlation test showed that there was a significant negative correlation between horizontal view-axis angle and C2-C7 angle. Conclusions: For patients with atlantoaxial instability diseases, the horizontal view-axis angle is expected to be a sagittal parameter to guide the intraoperative reduction and evaluate postoperative outcomes.